Synthesis of 3H, 2H4, and 14C‐MK 3814 (preladenant). (17th March 2017) - Hesk, D.; Borges, S.; Dumpit, R.; Hendershot, S.; Koharski, D.; McNamara, P.; Ren, S.; Saluja, S.; Truong, V.; Voronin, K.
Abstract : MK 3814 is a potent and selective antagonist of the A2a receptor. A2a receptor antagonists have the potential for the treatment of Parkinson disease. Three distinct isotopically labelled forms of MK 3814 were synthesized. [ 3 H]MK 3814 was prepared for a preliminary absorption, distribution, metabolism, and excretion data (ADME) evaluation of the compound and [ 14 C]MK 3814 for more definitive ADME work, including an absorption, metabolism, and excretion study in man. In addition, [ 2 H4 ]MK 3814 was prepared as an internal standard for a liquid chromatography mass spectrometry bioanalytical method. This paper discusses the synthesis of 3 isotopically labelled forms of MK 3814. Abstract : MK 3814 is a potent and selective antagonist of the A2a receptor. A2a ‐receptor antagonists have the potential for the treatment of Parkinson disease. Three distinct isotopically labelled forms of MK 3814 were synthesized. [3H]MK 3814 was prepared for a preliminary ADME evaluation of the compound and [14C]MK 3814 for more definitive ADME work, including an AME study in man. In addition, [2H4]MK 3814 was prepared as an internal standard for a LC‐MS bioanalytical method. The paper discusses the synthesis of 3 isotopically labelled forms of MK 3814.